2011
DOI: 10.2337/dc10-1796
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Insulin Delivery During Pregnancy Complicated by Type 1 Diabetes

Abstract: OBJECTIVEThis study evaluated closed-loop insulin delivery with a model predictive control (MPC) algorithm during early (12–16 weeks) and late gestation (28–32 weeks) in pregnant women with type 1 diabetes.RESEARCH DESIGN AND METHODSTen women with type 1 diabetes (age 31 years, diabetes duration 19 years, BMI 24.1 kg/m2, booking A1C 6.9%) were studied over 24 h during early (14.8 weeks) and late pregnancy (28.0 weeks). A nurse adjusted the basal insulin infusion rate from continuous glucose measurements (CGM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 18 publications
(24 reference statements)
3
99
0
1
Order By: Relevance
“…However, it should be noted that there are typically no differences in the total insulin doses infused or plasma insulin concentrations during conventional CSII and closed-loop insulin delivery [22,23]. More work is needed to extend and validate our findings and to further evaluate the risks and benefits of earlier insulin administration in pregnancy in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it should be noted that there are typically no differences in the total insulin doses infused or plasma insulin concentrations during conventional CSII and closed-loop insulin delivery [22,23]. More work is needed to extend and validate our findings and to further evaluate the risks and benefits of earlier insulin administration in pregnancy in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose control Closed-loop insulin delivery was used to achieve stable and comparable glycaemic conditions prior to meal consumption and throughout both study visits [22]. Satisfactory glyacemic control was maintained with no (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the data in the panel are from MPC studies-the green curve being from the same study by Russell and coauthors 16 shown in Figure 2A (repeated from Figure 1B) and the red and blue curves from studies performed by Hovorka and coauthors. 18,19 The first issue is how to compare two "closed-loop" algorithms in which one of the algorithms relies on a meal announcement with an open-loop meal bolus. The second, less obvious issue is how to decide which meal response is better-one that that goes up and down or one that remains flat.…”
Section: Review Of Available Clinical Datamentioning
confidence: 99%